THE EFFECT OF BALLOON BLOWING EXERCISE ON PEAKEXPIRATORY FLOW IN COPD PATIENTS - Enny Virda Yuniarti (International Journal of Nursing and Midwifery Science (IJNMS), 2025)
Chronic obstructive pulmonary disease remains a threat to global communities. COPD negatively affects health due to progressively reversible airflow obstruction. This disease has a prognosis that continues to worsen over time. Mortality in patients hospitalized for exacerbations with hypercapnia and acidosis is estimated at 10%. Mortality is 40% in patients who require mechanical ventilation one year after treatment and 49% mortality overall. The aim of this study is to analyze the effect of Balloon Blowing Exercise on peak expiratory flow in COPD patients. This research is a quantitative study with a pre-experimental design using a one-group pre-post test approach. The sample in this study consisted of COPD patients who met the inclusion criteria, namely not currently experiencing contagious pulmonary infections, totaling 30 respondents. The tools used for data collection are balloons, a peak flow meter to measure peak expiratory flow, and SPOs for the balloon blowing exercise breathing exercises. The research results obtained data showing the average value (Mean) of Peak Expiratory Flow (PEF) before the Balloon Blowing Exercise intervention was 90.83 lpm. With a standard deviation of 23.271, this indicates that the peak expiratory flow data in the pre-test group tends to have variations that are not too far from the average value and are largely clustered around the mean value of 90.83. The peak expiratory flow data of patients after the Balloon Blowing Exercise intervention (post-test) showed an average (Mean) PEF value of 103.53 lpm. With a standard deviation of 28.565, this indicates that the post-test PEF data distribution is not too far from its mean. The Wilcoxon Signed Rank Test results showed a Sig.(2-tailed) value of 0.000 < 0.05, meaning H0 is rejected and Ha is accepted, indicating that there is an effect of the Balloon Blowing Exercise on PEF in patients with COPD (Chronic Obstructive Pulmonary Disease). This exercise involves the use of respiratory muscles, thereby helping to strengthen those muscles and improve breathing efficiency. By improving ventilation, preventing water trapping, and strengthening the respiratory muscles, Balloon Blowing Exercise can reduce the work of breathing, which impacts the improvement of APE scores